An investigation into oral presentation anxiety of EFL advanced students at Can Tho University : - Võ, Thị Bảo Trân (Đại học Cần Thơ, 2011)
The current study aims to investigate the advanced students’ anxiety level about their oral presentation skills during test-taking time, then to clarify the correlation between learners’ anxiety and their performance in English oral test and the sources of their anxiety